Ene Reductase Enzymes for the Aromatisation of Tetralones and Cyclohexenones to Naphthols and Phenols. Issue 5 (17th February 2016) - Kelly, Paul P.; Lipscomb, David; Quinn, Derek J.; Lemon, Ken; Caswell, Jill; Spratt, Jenny; Kosjek, Birgit; Truppo, Matthew; Moody, Thomas S.
Abstract: Ene reductases (EREDs) have great potential as oxidation biocatalysts, as demonstrated by their efficient conversion of a number of tetralones to the corresponding naphthols. Of 96 enzymes tested, 57 were able to produce 2‐naphthol in this way. Further tests with substituted tetralones revealed typically high conversions up to >99%. The reactions were performed under mild conditions in aqueous buffer with only co‐solvent, biocatalyst and oxidation substrate required for conversion. Production of a methoxy‐substituted naphthol was also successfully performed on a gram scale, with 91% yield. This methodology provides a new avenue to produce substituted naphthols as valuable building blocks, with the possibility to extend the approach to the production of phenols also being demonstrated. Abstract :